Clinical value of esketamine combined with ropivacaine in rebound pain after brachial plexus block in patients with upper limb fractures - Zhu, Shiyao; Wang, Dan; Gao, Haiyan; Heng, Lei; Shui, Weikang; Zhu, Shanshan (Frontiers in Surgery, 2024)
ObjectiveTo analyze the clinical value of the combination of esketamine and ropivacaine in alleviating rebound pain in patients with upper limb fractures following brachial plexus block.MethodsA total of 149 patients with unilateral upper limb fractures who underwent open reduction and internal fixation surgery under brachial plexus block anesthesia from November 2021 to August 2022 were selected as the subjects for the study and randomly divided into the esketamine group (RNK group) and the ropivacaine group (R group). The incidence of rebound pain at 48 h postoperatively, intraoperative mean arterial pressure (MAP) and heart rate (HR), the onset time and duration of blockade, the Numeric Rating Scale (NRS) scores for pain at rest and with activity during the perioperative period, the dosage, numbers of compressions, and effective compressions of postoperative patient-controlled analgesia with sufentanil, and occurrence of adverse reactions were assessed and compared between the two groups.ResultsThe incidence of rebound pain in the RNK group was lower than that in the R group (P < 0.05). The RNK group exhibited higher MAP and HR at 5 min and 10 min after anesthesia compared to the R group (P < 0.05). The RNK group had faster onset time and longer duration of sensory and motor blockade compared to the R group (P < 0.05). The NRS scores at rest and with activity at 12 h and 24 h postoperatively in the RNK group were lower than those in the R group (P < 0.05). The total numbers of compressions, effective numbers of compressions, and dosage of sufentanil postoperatively were lower in the RNK group compared to the R group (P < 0.05). The incidence of adverse reactions in the RNK group did not differ significantly from that in the R group (P > 0.05).ConclusionsThe combination of esketamine and ropivacaine demonstrates a favorable preventive effect on rebound pain in patients with upper limb fractures following brachial plexus block, which is conducive to reducing the incidence of rebound pain, shortening the onset time of blockade, and prolonging the duration of blockade.Clinical Trial RegistrationClinicalTrials.gov, identifier (ChiCTR2100053035).